A compact substrate integrated waveguide CRLH leaky-wave antenna for S-band applications - Saravani S.; Chakrabarty C.K.; Din N.B.M.; Devi K.K.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antennas; Equivalent circuits; Microwave antennas; Scanning antennas; Traveling wave antennas; Waveguides; Compact leakywave antenna (LWA); Composite right/left-handed; CST microwave studio; E-field distributions; Equivalent circuit model; Full-wave simulations; Low cross polarization; Transition frequencies; Substrate integrated waveguides